(untitled) (Nepalese Journal of Cancer, 2026)
Introduction: Cancer patients require prolonged venous access for treatments, but repeated punctures can cause complications and distress, especially in children with fragile veins. Peripherally inserted central catheters like Broviac or Hickman pose infection risks and discomfort. Chemoports or sometimes also called vascular access port ( VAP) being subcutaneous in placement, offer fewer complications and greater comfort, making them preferable in paediatric population. Although chemoports have long been used for adults in our hospital, their application in children is recent. This study shares our experience with paediatric chemoports placement and its application, focusing on indications, insertion techniques, efficacy, safety, and early outcomes to assess their feasibility and benefits. Methods: This study included consecutive paediatric patients who underwent chemoport insertion between June 2023 and May 2025. The procedure was done under general anaesthesia with ultrasound-guided right IJV puncture. Catheter length was estimated between 8–11 cm, due to lack of intraoperative imaging. Postinsertion, patency was confirmed via aspiration/flushing, and placement verified by chest X-ray. Patients were monitored in the ICU before ward transfer. Nursing staff received regular training on port care. Followup data were prospectively recorded until port removal, death, or study end. Results: Fifty chemoports were inserted in 49 patients (32 males, 17 females), with a median age of 9 years, (IQR: 7.7–12). Acute leukaemia (ALL: 9, AML: 4) and osteosarcoma (8) were the most common diagnoses. Most (44/49) received ports before chemotherapy initiation. The right IJV (43/50) was the preferred access site. Nine patients completed treatment, with a median port duration of 354 days (IQR: 257–501); overall median duration was 215 days (IQR: 129–451). Disease outcome wise, 16 completed therapy, 22 remain on treatment and 11 patients even already died. Complications included intraoperative arrhythmia (38), ICD insertion (2), infections (3), premature removal (1), and reinsertion (1). Most issues were minor, with only one port removed due to recurrent sepsis. Conclusion: Chemoport insertion in paediatric oncology patients is safe and effective, with minimal complications. Standardized techniques and proper nursing care ensure successful outcomes. By improving patient comfort and treatment efficiency, chemoports serve as an excellent venous access option for paediatric cancer therapy, even in resource-limited settings like Nepal.